Konstruksi Pracetak Tahan Gempa Pada Rumah Susun Sewa Sederhana Universitas Muhammadiyah Malang - Ratih Sarwendah Komala Dewi (Media Teknik Sipil, 2011)
RUSUNAWA building of Muhammadiyah University of Malang with the precast construction system is much more profitable because the votes faster, cheaper, and efficient compared to the monolithic system construction. To re-planning is done (redesign) include precast components namely plates, beams, columns, and beam-column connection. Planning consists of, one-way reinforced concrete slab with dimensions 4.20m×2.50m×0.07m plus 0.05m is overtopping, reinforced concrete beams for the main beam 0.35m×0.40m and 0.30m×0.40m, column dimensions 0.40m×0.45m, and the connection used is a connection strands with grouting. Quality steel fy=1326Mpa strands, reinforcement quality BJTD screw 40, and fc=K400.The result of the calculation analysis, plates with a thickness of 12 cm consists of precast slab thickness of 7 cm and 5 cm thick overtopping the main reinforcement used D5-200 and the reinforcement for the D4-350, beam and main beam main reinforcement used and the cross bar 4D16 and f10-200mm, the column used and the cross bar reinforcement 6D22 and f10-400 mm. The connection is used, to column with strands 22 mm and length 920 mm, to block the distribution of 400 mm long 4D16. Connections in the grouting using Masterflow-95 on the columns and local casted on the beam-plate.Keywords: precast, plate, beams, columns, connections